Periodontal disease and associated factors in the adult and elderly population from Jundiaí City, Brazil - Marcela Di Moura Barbosa; Marília Jesus Batista; Evely Sartorti da Silva Morgan; Enilson Antonio Sallum; Marcio Zaffalon Casati; Karina Gonzales Silvério (Brazilian Journal of Oral Sciences, 2019)
Aim: This study assessed the prevalence of periodontal disease in the adult and elderly populations from Jundiaí City, and its association with individual social inequalities in a conceptual framework approach. Methods: The survey was conducted with a sample of 342 adults and 145 elderly, and periodontal disease was assessed based on the Community Periodontal Index (CPI) and Clinical Attachment Loss (CAL). A questionnaire addressing socio-demographic and behavioral variables, smoking and diabetes was included. Bivariate and multivariate analyses, using binary regression analyses, were carried out in a hierarchical approach with conceptual framework to reveal association among periodontal disease and social-demographic, smoking and diabetes variables. Results: One adult and fifty-six elderly who had lost all teeth were excluded from the sample. Mild periodontal disease (CAL ≤3 mm) was the condition more prevalent in the adult (74%) and elderly populations (60.6%). Adjusted analysis revealed that low educational level (OR 2.65, 95% CI 1.19-5.88), irregular use of tooth floss (OR 1.9, 95% CI 1.06-3.40), and smoking (OR 2.14, 95% CI 1.04-4.42) were independently associated with moderate/severe periodontal disease (CAL and Probing Depth ≥4 mm) in the adult group. For the elderly group, low educational levels (OR 0.16, 95% CI 0.04-0.58), use of public dental service (OR 5.32, 95% CI 1.23-23.03), and diabetes condition (OR 3.78, 95% CI 1.20-11.91) were significantly associated with periodontal disease. Conclusion: In conclusion, the data showed that education level, smoking habits, diabetes, use of dental floss and type of dental service are factors associated to moderate/severe periodontal disease among Brazilians from Jundiaí City.